ANALISIS KEUNTUNGAN PENGRAJIN TEMPE (Studi Kasus Pengrajin Tempe Di Jalan Sanan Kota Malang) - Yoris Moragie (Fakultas Pertanian, 2021)
Tempe is a typical Indonesian food, even tempeh is also known to the international community According to Hermana (1985), tempe is a processed soy protein rich. The purpose of this research is 1) to know the socio-economic factors that affect the profits of tempe craftsmen in Sanan Malang City, 2) to know how the influence of socio-economic factors to the advantage of skilled artisans Sanan Malang, 3) To know whether in Making tempe provide benefits or not to tempe craftsmen in Sanan Malang. The hypothesis of this research are: 1) The cost of raw materials and the amount of production is expected to affect the profit of pengerajin tempe in Sanan Malang City, 2) Allegedly socio-economic factors (education, age, number of family dependents, amount of production, Raw materials) affect the profits of tempe craftsmen in Sanan Malang. 3) tempe craftsmen in Sanan Malang city advantageous.